MENGATASI KONFLIK INTERNAL PADA PASANGAN MENIKAH DENGAN KONSELING KELUARGA - Hasanah, Iswatun; Wahyuningrum, Sri Rizqi (Journal of Innovation Research and Knowledge, 2024)
The complexity of internal conflicts between married couples often requires the presence of professionals to resolve problems and increase the psychological intimacy of couples. This research aims to understand the realization of family guidance and counseling services carried out by the IAIN Madura counseling service center for families who need help. Using a curative retrospective case study approach allows for follow-up efforts to improve a case with research subjects 3 families using a purposive sampling technique. Data collection uses open interviews, direct observation, archival service records, and documentation, as well as data analysis using a spiral model. The results of the research showed that 2 research subjects succeeded in resolving internal conflicts after receiving family counseling services with a minimum of 4 meetings, and 1 research subject was not able to resolve the conflict they experienced and needed a referral to another professional because the anxiety they experienced was experiencing an abnormality. The research conclusion is that family counseling services can help overcome internal conflicts in couples to increase and maintain harmony in the family.